Synthesis, Characterization and Biochemical Activity of Dinuclear Cu(II)/Ni(II)/Co(II) and Tetranuclear Cu(II) Complexes of Schiff Base - Karabocek, Nevin; Eski, Pinar; Baskan, Oya; Karabocek, Serdar (Asian Journal of Chemistry, 2011)
A new Schiff base bis-[2,2'-1,2-phenylenebis[nitrilo(E)methylylidene]diphenol] (3) was prepared by reacting biphenyl-3,3',4,4'-tetramine (1) and salicylaldehyde (2) in EtOH. The new ligand was characterized by elemental analyses, 1H and 13C-NMR, IR and mass spectral studies. Dinuclear copper(II), nickel(II), cobalt(II) and tetranuclear copper(II) complexes of ligand were prepared and characterized by elemental analyses, magnetic moments, IR, UV-VIS and mass spectral studies. Metal:ligand ratio was found as 2:1 in the dinuclear metal complexes. Elemental analyses, stoichiometric and spectroscopic data of the metal complexes indicated that the metal ions were coordinated to the nitrogen atoms and oxygen atoms of Schiff base ligand. Testing the bacteriostatic diameter can test the susceptibility of a bacterium towards a drug. The ligand and its metal complexes had no inhibitor activity against G(-) E. coli. But the content was used 0.2 % ligand and its metal complexes had inhibitory activity against G(-) S. aureus and P. aeruginosa.